2002
DOI: 10.1079/phn2001251
|View full text |Cite
|
Sign up to set email alerts
|

Defining nutritional status of women in developing countries

Abstract: Objective: To define a de facto reference body mass index (BMI) for women in developing countries and compare its performance with the Quetelet BMI. Design: A logarithmic equation for elite wt/ht references was developed using the weight (wt) and height (ht) of 10 524 non-pregnant elite mothers. Functional outcomes were compared using both BMIs. Setting: Forty-six national surveys from 36 developing countries. Subjects: Mothers 15 -49 years old. Results: The de facto reference standard deviation showed 2.2% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…In the context of sub‐Saharan Africa, excluding women with poor nutritional status or antenatal infections from the study population would create an ‘artificially healthy’ pregnancy cohort, and produce mean and centile values that overestimate the true source population fetal weight. The prevalence of undernutrition and malaria parasitemia observed in this Kinshasa population is similar to that of other sub‐Saharan African antenatal populations22, 23. However, the antenatal HIV prevalence in Kinshasa is among the lowest in the region24 and all enrolled women received monthly antenatal care including aggressive antimalarial treatment as part of the parent study.…”
Section: Discussionsupporting
confidence: 71%
“…In the context of sub‐Saharan Africa, excluding women with poor nutritional status or antenatal infections from the study population would create an ‘artificially healthy’ pregnancy cohort, and produce mean and centile values that overestimate the true source population fetal weight. The prevalence of undernutrition and malaria parasitemia observed in this Kinshasa population is similar to that of other sub‐Saharan African antenatal populations22, 23. However, the antenatal HIV prevalence in Kinshasa is among the lowest in the region24 and all enrolled women received monthly antenatal care including aggressive antimalarial treatment as part of the parent study.…”
Section: Discussionsupporting
confidence: 71%
“…Although different thresholds of BMI have been used to define underweight, the present findings are in line with most studies . They are also consistent with findings among women without HIV infection . A study in the Côte d'Ivoire of 326 HIV‐infected pregnant women (46% receiving cART in pregnancy) found that low BMI (<25) at delivery increased the risk of low delivery weight by a factor of 2.43 (95% CI, 1.20–4.91; P =0.013) .…”
Section: Discussionsupporting
confidence: 90%
“…16,24 They are also consistent with findings among women without HIV infection. 25 Women who received a single dose of NPV before delivery or no treatment before delivery. b Women who received cART before pregnancy or during the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65] Women with low prepregnancy BMI, both in developing and developed countries, are at risk for preterm birth and intrauterine growth retardation. [64][65][66][67][68] In addition, women with low prepregnancy BMI appear to be more sensitive to additional risk factors, such as smoking and psychosocial risk factors 69,70 and to benefit more from zinc supplementation during pregnancy. 69 Neggers and Goldenberg 71 have discussed the mechanism whereby low maternal prepregnancy BMI affects pregnancy outcome.…”
Section: Maternal Bmi and Nutritionmentioning
confidence: 99%